An analysis An analysis of Intructional Media for English Teachers During The Pandemic (case study SMA Bukit Raya) - Rinjani Eka Putri; Marhamah (JTP - Jurnal Teknologi Pendidikan, 2021)
The pandemic that has hit all over the world is very disturbing, especially in the field of education which requires learning in schools to be sent home. the current pandemic has led schools to conduct learning through technology media. which requires teachers and students to use the best applications during online learning, due to the very concerning impact of the Covid-19 outbreak which requires students to learn from home. Online learning currently uses supportive applications so that it can be carried out well. Supporting applications in learning virtually include several application media such as: Whastapp Group features which can display videos, images and others, Google Classroom features can display a time set by the teacher to students or have a time limit so that students are more punctual, Google features Meet can show face to face without any time limit. The zoom feature can also be face-to-face online but has time and other application media limitations. therefore teachers must be careful in choosing the applications used during online learning at this time. however, there are several obstacles in conducting online learning at this time, namely the network in remote schools which results in student delays in collecting assignments online